If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -17 = 2x + 3 Reorder the terms: -17 + 6x = 2x + 3 Reorder the terms: -17 + 6x = 3 + 2x Solving -17 + 6x = 3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -17 + 6x + -2x = 3 + 2x + -2x Combine like terms: 6x + -2x = 4x -17 + 4x = 3 + 2x + -2x Combine like terms: 2x + -2x = 0 -17 + 4x = 3 + 0 -17 + 4x = 3 Add '17' to each side of the equation. -17 + 17 + 4x = 3 + 17 Combine like terms: -17 + 17 = 0 0 + 4x = 3 + 17 4x = 3 + 17 Combine like terms: 3 + 17 = 20 4x = 20 Divide each side by '4'. x = 5 Simplifying x = 5
| 8(x-3)=-7(x+2)+47 | | r-1=4+6r | | 32+8x=38+7x | | x*x+7x=11 | | 3x^(1/2)-13x^(1/4)-30=0 | | 0=16t^2+60t+4 | | -3=3(6x)+4x | | X^2x=24 | | 3x^1/2-13x^1/4-30=0 | | 6(n+3)=30 | | 7/3×13/8 | | 2/4y-1=1/4 | | y=16t^2+60t+4 | | b-3a= | | -4x7/-14 | | 7/3×13/8= | | -3(n+5)-5n=-5n-39 | | 1.2p+3.7=34.6 | | 10+p=25 | | 4-10r=56 | | -70-6x=-12x+20 | | 3p+6=24 | | tan(2x)-2tanx=0 | | 4x+4=3x-3.5 | | 28p=28 | | -3+-5+8= | | X-72=7x+88 | | X-6-7=-12+2x | | 5(x+3)-4(x+1)=0 | | x^2+4x+1-x^2+17=0 | | ln(3t)=1.9 | | 3(1-3x)=14-8x |